A high-performance flexible wood electrode material and its preparation method and application

By treating wood with potassium hydroxide and hydrogen peroxide and introducing MXene, the problem of difficulty in both flexibility and conductivity of existing wood electrodes is solved, and the preparation of high-performance flexible wood electrodes is realized, which expands its application in the field of flexible energy storage devices.

CN118888346BActive Publication Date: 2025-03-21NORTHEAST FORESTRY UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410935373.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-12
Publication Date
2025-03-21
Estimated Expiration
2044-07-12

AI Technical Summary

Technical Problem

The existing wood-derived electrode materials are difficult to be flexible and conductive. The carbonization process has high energy consumption and the prepared carbonaceous electrodes are not brittle enough, which limits their application in the field of flexible energy storage devices.

Method used

Treating wood by potassium hydroxide and hydrogen peroxide gives it flexibility characteristics, and introducing MXene as the main conductive substance, so as to achieve both flexibility and conductivity of wood electrodes through the loading of nanocellulose.

Benefits of technology

High-performance flexible wood electrodes are realized, high-energy carbonization process is avoided, the application of wood electrodes in the field of flexible energy storage devices is expanded, and the preparation process is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118888346B_ABST
    Figure CN118888346B_ABST
Patent Text Reader

Abstract

A high-performance flexible wood electrode material and its preparation method and application belong to the technical field of electrode material preparation. In order to improve the flexibility of carbonaceous electrodes, the present invention includes the preparation of MXene suspension; chemical treatment of basswood: soak natural basswood in a certain concentration of potassium hydroxide solution for 8-12 hours under vacuum environment, take it out and put it into hydrogen peroxide solution for 12-14 hours, then wash the basswood with deionized water for many times, and place the washed basswood in tert-butyl alcohol for solvent exchange, and then freeze-dry to obtain chemically treated basswood; immerse the chemically treated basswood in a certain concentration of nanocellulose suspension, take it out and freeze-dry it to obtain a freeze-dried sample. Add a certain mass of pure water to the prepared MXene suspension, then add the freeze-dried sample after ultrasonic dispersion for a certain time, soak it in a vacuum environment and then freeze-dry it to obtain a flexible MXene-basswood electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrode material preparation, and in particular relates to a high-performance flexible wood electrode material and a preparation method and application thereof. Background Art

[0002] Wood-derived electrode materials for energy storage devices have attracted extensive attention. However, due to the natural rigidity and electrical insulation of wood, it is difficult to achieve wood electrodes that are both flexible and conductive. The existing technology carbonizes wood blocks to form self-supporting electrodes to obtain rich pore structures and conductivity, but the carbonization process consumes a lot of energy, and the resulting carbonaceous electrodes are brittle, making them difficult to apply in the field of flexible energy storage devices, limiting their application. Summary of the invention

[0003] The problem to be solved by the invention is to improve the flexibility of a carbonaceous electrode, and a high-performance flexible wood electrode material and a preparation method and application thereof are provided.

[0004] To achieve the above object, the present invention is implemented through the following technical solutions:

[0005] A method for preparing a high-performance flexible wood electrode material comprises the following steps:

[0006] S1. Preparation of MXene suspension: Ti3AlC2 was slowly added to the etching solution according to a certain material-liquid ratio, stirred at 35-40°C for 24-30 hours, and then the obtained solution was centrifuged at 3500-4000rpm. The precipitate obtained by centrifugation was washed with deionized water until the pH was 6.0-6.5, and then the precipitate was ultrasonicated under argon protection for 1-1.5 hours, and then centrifuged for 1-1.5 hours to remove the unstratified precipitate to obtain dark green Ti3C2T x Suspension;

[0007] S2. Chemical treatment of basswood: soaking natural basswood in a certain concentration of potassium hydroxide solution for 8-12 hours under vacuum, taking it out and then placing it in a certain concentration of hydrogen peroxide solution for 12-14 hours, then washing the basswood with deionized water several times, and placing the washed basswood in tert-butyl alcohol for 12-14 hours for solvent exchange, and then freeze-drying to obtain chemically treated basswood;

[0008] S3. Preparation of flexible MXene-basswood electrode: immerse the chemically treated basswood obtained in step S2 into a nanocellulose suspension of a certain concentration, soak it in a vacuum environment for 8-12 hours to obtain a sample, take it out and freeze-dry it to obtain a freeze-dried sample;

[0009] The MXene suspension prepared in step S1 is added with a certain mass of deionized water, and then ultrasonically dispersed for a certain period of time before adding the freeze-dried sample, soaking in a vacuum environment for 12-14 hours and then freeze-drying, and the soaking MXene suspension and then freeze-drying process are repeated three times to obtain a flexible MXene-basswood electrode.

[0010] Furthermore, the etching solution in step S1 is prepared by adding 1.0 g of LiF into 20 mL of 9 M hydrochloric acid aqueous solution, and stirring at 500 rpm for 10 minutes to obtain a uniform etching solution.

[0011] Furthermore, in step S1, the material-liquid ratio of Ti3AlC2 and etching solution is 1g:20-25ml, the ultrasonic power is 300W, and the centrifugal speed is 3500rpm.

[0012] Furthermore, in step S2, the thickness of the natural basswood is 1-5 mm, the concentration of the potassium hydroxide solution is 5-15 wt %, and the concentration of the hydrogen peroxide solution is 15-30 wt %.

[0013] Furthermore, the freeze-drying conditions in step S2 are 1 Pa, -50°C, and the freeze-drying time is 12-48 hours.

[0014] Furthermore, in step S3, the concentration of nanocellulose is 0.5-0.8 wt %, the nanocellulose is cellulose with a diameter of 3-10 nm and a length of 400-800 nm, and the vacuum environment is 0.1-1.0 MPa and 25° C.

[0015] Furthermore, in step S3, the concentration of the MXene suspension obtained by adding a certain mass of deionized water to the MXene suspension prepared in step S1 is 5 mg / mL, the ultrasonic time is 10-30 minutes, the freeze-drying conditions are 1 Pa, -50°C, and the freeze-drying time is 12-48 hours.

[0016] A method for preparing a high-performance flexible wood electrode material provides a high-performance flexible wood electrode material, wherein the maximum bending angle of the electrode is 135°.

[0017] A method for preparing a high-performance flexible wood electrode material and an application of the prepared high-performance flexible wood electrode material are used in supercapacitors, zinc ion hybrid capacitors, lithium ion batteries, zinc batteries, zinc-air batteries, and sodium ion batteries.

[0018] Furthermore, the flexible MXene-basswood electrode was used as the cathode, the metal zinc plate as the anode, and the polyacrylamide / ZnSO4 gel as the electrolyte to assemble a zinc ion hybrid capacitor.

[0019] Beneficial effects of the present invention:

[0020] The method for preparing a high-performance flexible wood electrode material described in the present invention uses potassium hydroxide and hydrogen peroxide treatment to give wood flexibility, and further introduces MXene with excellent electrochemical properties, thereby realizing a wood electrode that is both flexible and conductive, avoiding the use of high-energy consumption carbonization processes and the preparation of brittle carbonized wood, and expanding the application of wood electrodes in the field of flexible energy storage devices.

[0021] In the method for preparing a high-performance flexible wood electrode material described in the present invention, the main conductive material that gives the wood excellent electrochemical properties is MXene, and there is no need to introduce a polypyrrole component, so the preparation process is relatively simple. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Comparative photos of the flexibility of a high-performance flexible wood electrode material described in the present invention, wherein group (a) is basswood, group (b) is chemically treated basswood, and group (c) is a flexible MXene-basswood electrode;

[0023] Figure 2 The SEM photos of basswood used in the present invention, wherein group (a) is a photo magnified 200 times, and group (b) is a photo magnified 3000 times;

[0024] Figure 3 These are SEM photos of the chemically treated basswood of the present invention, wherein group (a) is a photo magnified 200 times, and group (b) is a photo magnified 2500 times;

[0025] Figure 4 These are SEM photos of the flexible MXene-basswood electrode of the present invention, wherein group (a) is a photo magnified 1000 times, and group (b) is a photo magnified 5000 times;

[0026] Figure 5 These are test photos of the zinc ion hybrid battery assembled with the flexible MXene-basswood electrode of the present invention, wherein (a) is a photo of the zinc ion hybrid battery assembled with the MXene-basswood electrode, (b) is a cyclic voltammetry curve, (c) is a constant current charge and discharge curve, (d) is the capacitance retention rate after 5000 cycles, and (e) is a schematic diagram of a photo of a power supply used as a thermometer and hygrometer;

[0027] Figure 6 The cyclic voltammetry curves of the zinc ion hybrid capacitor assembled with the flexible MXene-basswood electrode of the present invention at different bending angles, wherein (a) is the cyclic voltammetry curve, and (b) is a schematic diagram of the photos at different bending angles. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the specific embodiments described are only part of the embodiments of the present invention, rather than all of the specific embodiments. The components of the specific embodiments of the present invention described and shown in the drawings herein can be arranged and designed in various different configurations, and the present invention can also have other embodiments.

[0029] Therefore, the following detailed description of the specific embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected specific embodiments of the present invention. Based on the specific embodiments of the present invention, all other specific embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.

[0030] In order to further understand the content, features and effects of the present invention, the following specific implementation methods are given as examples, and the attached Figure 1 -Attached Figure 6 The detailed instructions are as follows:

[0031] Embodiment 1:

[0032] A method for preparing a high-performance flexible wood electrode material comprises the following steps:

[0033] S1. Preparation of MXene suspension: Ti3AlC2 was slowly added to the etching solution according to a certain material-liquid ratio, stirred at 35°C for 24 hours, and then the obtained solution was centrifuged at 3500rpm. The precipitate obtained by centrifugation was washed with deionized water until the pH was 6.0, and then the precipitate was ultrasonicated for 1 hour under argon protection, and then centrifuged for 1 hour to remove the unstratified precipitate to obtain dark green Ti3C2T x Suspension;

[0034] Furthermore, the etching solution in step S1 is prepared by adding 1.0 g of LiF into 20 mL of 9 M hydrochloric acid aqueous solution, and stirring at 500 rpm for 10 minutes to obtain a uniform etching solution.

[0035] Furthermore, in step S1, the material-liquid ratio of Ti3AlC2 to etching solution is 1g:20ml, and the ultrasonic power is 300W.

[0036] S2. Chemical treatment of basswood: natural basswood was immersed in a potassium hydroxide solution of a certain concentration for 8 hours under vacuum, and then placed in a hydrogen peroxide solution of a certain concentration for 12 hours, and then washed with deionized water several times, and the washed basswood was placed in tert-butyl alcohol for 12 hours for solvent exchange, and then freeze-dried to obtain chemically treated basswood;

[0037] Furthermore, in step S2, the thickness of the natural basswood is 1 mm, the concentration of the potassium hydroxide solution is 5 wt %, and the concentration of the hydrogen peroxide solution is 30 wt %.

[0038] Furthermore, the freeze-drying conditions in step S2 are 1 Pa, -50°C, and the freeze-drying time is 12 hours.

[0039] S3. Preparation of flexible MXene-basswood electrode: immerse the chemically treated basswood obtained in step S2 into a nanocellulose suspension of a certain concentration, soak it in a vacuum environment at 1.0 MPa and 25°C for 8 hours to obtain a sample, take it out and freeze-dry it to obtain a freeze-dried sample;

[0040] The MXene suspension prepared in step S1 is added with a certain mass of deionized water, and then ultrasonically dispersed for a certain period of time and then the freeze-dried sample is added, and then immersed in a vacuum environment at 1.0 MPa and 25°C for 12 hours and then freeze-dried. The soaking MXene suspension and then freeze-drying process is repeated three times to obtain a flexible MXene-basswood electrode.

[0041] Furthermore, in step S3, the concentration of nanocellulose is 0.5 wt %, and the nanocellulose is cellulose with a diameter of 3-10 nm and a length of 400-800 nm.

[0042] Furthermore, in step S3, the concentration of the MXene suspension obtained by adding a certain mass of deionized water to the MXene suspension prepared in step S1 is 5 mg / mL, the ultrasonic time is 10 minutes, the freeze-drying conditions are 1 Pa, -50°C, and the freeze-drying time is 12 hours.

[0043] The method for preparing a high-performance flexible wood electrode material described in this embodiment prepares a high-performance flexible wood electrode material, and the maximum bending angle of the electrode is 135°.

[0044] A high-performance flexible wood electrode material prepared by the method for preparing a high-performance flexible wood electrode material described in this embodiment, Figure 1 Comparative photos of the flexibility of a high-performance flexible wood electrode material described in this embodiment, wherein group (a) is basswood, group (b) is chemically treated basswood, and group (c) is a flexible MXene-basswood electrode; Figure 1It can be seen that natural basswood has great rigidity and is easily broken under external forces, making it unsuitable for use as a substrate for flexible electrodes. Chemically treated basswood treated with potassium hydroxide and hydrogen peroxide retains the macroscopic morphology of the original basswood, but exhibits excellent flexibility, which is in sharp contrast to the original brittle basswood and can be used as a substrate for flexible electrodes.

[0045] Figure 2 The SEM photos of basswood used in this embodiment, wherein group (a) is a photo magnified 200 times, and group (b) is a photo magnified 3000 times; Figure 3 These are SEM photos of the chemically treated basswood described in this embodiment, wherein group (a) is a photo magnified 200 times, and group (b) is a photo magnified 2500 times; Figure 4 The SEM photos of the flexible MXene-basswood electrode described in this embodiment, wherein group (a) is a 1000-fold magnified photo, and group (b) is a 5000-fold magnified photo; Figure 2-Figure 4 It can be seen that compared with the original basswood, the large amount of hemicellulose removed and the small amount of rigid lignin removed destroyed the dense cell wall structure of the original basswood. The cell wall of the chemically treated basswood became significantly thinner and showed a certain degree of fragmentation, which gave the chemically treated basswood flexibility and a higher specific surface area, providing convenience for the high loading of MXene. Nanocellulose acts as a bridge to achieve uniform loading of MXene nanosheets on the surface of the wood cell wall. A large amount of hydrogen bonding increases the interfacial bonding between MXene and the matrix, giving the electrode excellent electrochemical properties.

[0046] Figure 5 These are test photos of the zinc ion hybrid battery assembled with the flexible MXene-basswood electrode described in this embodiment, wherein (a) is a photo of the zinc ion hybrid battery assembled with the MXene-basswood electrode, (b) is a cyclic voltammetry curve, (c) is a constant current charge and discharge curve, (d) is a capacitance retention rate after 5000 cycles, and (e) is a schematic photo of a power supply used as a thermometer and hygrometer; Figure 5 The figure shows a schematic diagram of the structure of a zinc ion hybrid capacitor assembled with a flexible MXene-basswood cathode, a pure zinc plate anode and a polyacrylamide (PAM) / ZnSO4 hydrogel electrolyte. The cyclic voltammetric characteristic curves obtained at different rates show similar parallelogram-like shapes and have consistent redox peak positions. The constant current charge and discharge curves at different current densities show an approximately symmetrical triangle, indicating that the energy storage system has excellent electrochemical reversibility and adaptability to electrochemical reaction kinetics. After 5000 cycle tests, the capacitance retention rate of the capacitor is still above 95%, and the assembled zinc ion hybrid capacitor can be used as a power supply for a thermometer and hygrometer.

[0047] Figure 6The cyclic voltammetry curves of the zinc ion hybrid capacitor assembled with the flexible MXene-basswood electrode described in this embodiment at different bending angles, wherein (a) is a cyclic voltammetry curve, and (b) is a schematic diagram of photos at different bending angles; Figure 6 It can be seen that the cyclic voltammetric characteristic curves measured when the capacitor is bent at different angles show almost consistent parallelogram-like shapes and redox peak positions, indicating that the zinc ion hybrid capacitor assembled with flexible MXene-basswood electrodes has excellent flexibility and is expected to be used as a power source for wearable electronic devices.

[0048] Embodiment 2:

[0049] A method for preparing a high-performance flexible wood electrode material comprises the following steps:

[0050] S1. Preparation of MXene suspension: Ti3AlC2 was slowly added to the etching solution according to a certain material-liquid ratio, stirred at 36°C for 24 hours, and then the obtained solution was centrifuged at 4000 rpm. The precipitate obtained by centrifugation was washed with deionized water until the pH was 6.5, and then the precipitate was ultrasonicated for 1.5 hours under argon protection, and then centrifuged for 1.5 hours to remove the unstratified precipitate to obtain dark green Ti3C2T x Suspension;

[0051] Furthermore, the etching solution in step S1 is prepared by adding 1.0 g of LiF into 20 mL of 9 M hydrochloric acid aqueous solution, and stirring at 500 rpm for 10 minutes to obtain a uniform etching solution.

[0052] Furthermore, in step S1, the material-liquid ratio of Ti3AlC2 to etching solution is 1g:25ml, and the ultrasonic power is 300W.

[0053] S2. Chemical treatment of basswood: natural basswood was immersed in a potassium hydroxide solution of a certain concentration for 12 hours under a vacuum environment, and then placed in a hydrogen peroxide solution of a certain concentration for 14 hours, and then washed with deionized water several times, and the washed basswood was placed in tert-butyl alcohol for 14 hours for solvent exchange, and then freeze-dried to obtain chemically treated basswood;

[0054] Furthermore, in step S2, the thickness of the natural basswood is 2 mm, the concentration of the potassium hydroxide solution is 10 wt %, and the concentration of the hydrogen peroxide solution is 30 wt %.

[0055] Furthermore, the freeze-drying conditions in step S2 are 1 Pa, -50°C, and the freeze-drying time is 18 hours.

[0056] S3. Preparation of flexible MXene-basswood electrode: immerse the chemically treated basswood obtained in step S2 into a nanocellulose suspension of a certain concentration, soak for 12 hours in a vacuum environment at 0.1 MPa and 25°C to obtain a sample, take it out and freeze-dry it to obtain a freeze-dried sample;

[0057] The MXene suspension prepared in step S1 is added with a certain mass of deionized water, and then ultrasonically dispersed for a certain period of time before adding the freeze-dried sample. The sample is soaked in a vacuum environment at 0.1 MPa and 25°C for 14 hours and then freeze-dried. The soaking MXene suspension and then freeze-drying process is repeated three times to obtain a flexible MXene-basswood electrode.

[0058] Furthermore, in step S3, the concentration of nanocellulose is 0.5-0.8 wt %, and the nanocellulose is cellulose with a diameter of 3-10 nm and a length of 400-800 nm.

[0059] Furthermore, in step S3, the concentration of the MXene suspension obtained by adding a certain mass of deionized water to the MXene suspension prepared in step S1 is 5 mg / mL, the ultrasonic time is 15 minutes, the freeze-drying conditions are 1 Pa, -50°C, and the freeze-drying time is 18 hours.

[0060] The method for preparing a high-performance flexible wood electrode material described in this embodiment prepares a high-performance flexible wood electrode material, and the maximum bending angle of the electrode is 135°.

[0061] Embodiment 3:

[0062] A method for preparing a high-performance flexible wood electrode material comprises the following steps:

[0063] S1. Preparation of MXene suspension: Ti3AlC2 was slowly added to the etching solution according to a certain material-liquid ratio, stirred at 36°C for 25 hours, and then the obtained solution was centrifuged at 3800 rpm. The precipitate obtained by centrifugation was washed with deionized water until the pH was 6.1, and then the precipitate was ultrasonicated for 1.2 hours under argon protection, and then centrifuged for 1.2 hours to remove the unstratified precipitate to obtain dark green Ti3C2T x Suspension;

[0064] Furthermore, the etching solution in step S1 is prepared by adding 1.0 g of LiF into 20 mL of 9 M hydrochloric acid aqueous solution, and stirring at 500 rpm for 10 minutes to obtain a uniform etching solution.

[0065] Furthermore, in step S1, the material-liquid ratio of Ti3AlC2 and etching solution is 1g:22ml, the ultrasonic power is 300W, and the centrifugal speed is 3500rpm.

[0066] S2. Chemical treatment of basswood: natural basswood was immersed in a potassium hydroxide solution of a certain concentration for 10 hours under vacuum, and then placed in a hydrogen peroxide solution of a certain concentration for 13 hours, and then washed with deionized water several times, and the washed basswood was placed in tert-butyl alcohol for 13 hours for solvent exchange, and then freeze-dried to obtain chemically treated basswood;

[0067] Furthermore, in step S2, the thickness of the natural basswood is 4 mm, the concentration of the potassium hydroxide solution is 6 wt %, and the concentration of the hydrogen peroxide solution is 26 wt %.

[0068] Furthermore, the freeze-drying conditions in step S2 are 1 Pa, -50°C, and the freeze-drying time is 36 hours.

[0069] S3. Preparation of flexible MXene-basswood electrode: immerse the chemically treated basswood obtained in step S2 into a nanocellulose suspension of a certain concentration, soak for 8-12 hours in a vacuum environment of 0.2 MPa and 25°C to obtain a sample, take it out and freeze-dry it to obtain a freeze-dried sample;

[0070] The MXene suspension prepared in step S1 is added with a certain mass of deionized water, and then the freeze-dried sample is added after ultrasonic dispersion for a certain period of time. The sample is soaked in a vacuum environment at 0.2 MPa and 25°C for 12 hours and then freeze-dried. The soaking MXene suspension and then freeze-drying process is repeated three times to obtain a flexible MXene-basswood electrode.

[0071] Furthermore, in step S3, the concentration of nanocellulose is 0.5-0.8 wt %, and the nanocellulose is cellulose with a diameter of 3-10 nm and a length of 400-800 nm.

[0072] Furthermore, in step S3, the concentration of the MXene suspension obtained by adding a certain mass of deionized water to the MXene suspension prepared in step S1 is 5 mg / mL, the ultrasonic time is 12 minutes, the freeze-drying conditions are 1 Pa, -50°C, and the freeze-drying time is 36 hours.

[0073] The method for preparing a high-performance flexible wood electrode material described in this embodiment prepares a high-performance flexible wood electrode material, and the maximum bending angle of the electrode is 135°.

[0074] Embodiment 4:

[0075] A method for preparing a high-performance flexible wood electrode material comprises the following steps:

[0076] S1. Preparation of MXene suspension: Ti3AlC2 was slowly added to the etching solution according to a certain material-liquid ratio, stirred at 37°C for 26 hours, and then the obtained solution was centrifuged at 3600 rpm. The precipitate obtained by centrifugation was washed with deionized water until the pH was 6.2, and then the precipitate was ultrasonicated for 1 hour under argon protection, and then centrifuged for 1 hour to remove the unstratified precipitate to obtain dark green Ti3C2T x Suspension;

[0077] Furthermore, the etching solution in step S1 is prepared by adding 1.0 g of LiF into 20 mL of 9 M hydrochloric acid aqueous solution, and stirring at 500 rpm for 10 minutes to obtain a uniform etching solution.

[0078] Furthermore, in step S1, the material-liquid ratio of Ti3AlC2 and etching solution is 1 g:24 ml, the ultrasonic power is 300 W, and the centrifugal speed is 3500 rpm.

[0079] S2. Chemical treatment of basswood: natural basswood was immersed in a potassium hydroxide solution of a certain concentration for 11 hours under vacuum, and then placed in a hydrogen peroxide solution of a certain concentration for 12 hours, and then washed with deionized water several times, and the washed basswood was placed in tert-butyl alcohol for 12 hours for solvent exchange, and then freeze-dried to obtain chemically treated basswood;

[0080] Furthermore, in step S2, the thickness of the natural basswood is 5 mm, the concentration of the potassium hydroxide solution is 7 wt %, and the concentration of the hydrogen peroxide solution is 30 wt %.

[0081] Furthermore, the freeze-drying conditions in step S2 are 1 Pa, -50°C, and the freeze-drying time is 48 hours.

[0082] S3. Preparation of flexible MXene-basswood electrode: immerse the chemically treated basswood obtained in step S2 into a nanocellulose suspension of a certain concentration, soak for 10 hours in a vacuum environment at 0.5 MPa and 25°C to obtain a sample, take it out and freeze-dry it to obtain a freeze-dried sample;

[0083] The MXene suspension prepared in step S1 is added with a certain mass of deionized water, and then ultrasonically dispersed for a certain period of time before adding the freeze-dried sample. The sample is soaked in a vacuum environment at 0.5 MPa and 25°C for 12 hours and then freeze-dried. The soaking MXene suspension and then freeze-drying process is repeated three times to obtain a flexible MXene-basswood electrode.

[0084] Furthermore, in step S3, the concentration of nanocellulose is 0.7 wt %, and the nanocellulose is cellulose with a diameter of 3-10 nm and a length of 400-800 nm.

[0085] Furthermore, in step S3, the concentration of the MXene suspension obtained by adding a certain mass of deionized water to the MXene suspension prepared in step S1 is 5 mg / mL, the ultrasonic time is 14 minutes, the freeze-drying conditions are 1 Pa, -50°C, and the freeze-drying time is 48 hours.

[0086] The method for preparing a high-performance flexible wood electrode material described in this embodiment prepares a high-performance flexible wood electrode material, and the maximum bending angle of the electrode is 135°.

[0087] Embodiment 5:

[0088] An application of a high-performance flexible wood electrode material prepared by the preparation method of a high-performance flexible wood electrode material described in one of Examples 1 to 4 is used in supercapacitors, zinc ion hybrid capacitors, lithium ion batteries, zinc batteries, zinc-air batteries, and sodium ion batteries.

[0089] Furthermore, the flexible MXene-basswood electrode was used as the cathode, the metal zinc plate as the anode, and the polyacrylamide / ZnSO4 gel as the electrolyte to assemble a zinc ion hybrid capacitor.

[0090] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0091] Although the present application has been described above with reference to specific embodiments, various modifications may be made thereto and parts thereof may be replaced with equivalents without departing from the scope of the present application. In particular, as long as there is no structural conflict, the various features in the specific embodiments disclosed in the present application may be used in combination with each other in any manner, and the fact that these combinations are not exhaustively described in this specification is only for the sake of omitting space and saving resources. Therefore, the present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A method for preparing a high-performance flexible wood electrode material, characterized in that: The steps include: S1. Preparation of MXene suspension: Ti3AlC2 was slowly added to the etching solution according to a certain material-liquid ratio, stirred at 35-40°C for 24-30 hours, and then the obtained solution was centrifuged at 3500-4000rpm. The precipitate obtained by centrifugation was washed with deionized water until the pH was 6.0-6.5, and then the precipitate was ultrasonicated under argon protection for 1-1.5 hours, and then centrifuged for 1-1.5 hours to remove the unstratified precipitate to obtain dark green Ti3C2T x Suspension; S2. Chemical treatment of basswood: soaking natural basswood in a certain concentration of potassium hydroxide solution for 8-12 hours under vacuum, taking it out and then placing it in a certain concentration of hydrogen peroxide solution for 12-14 hours, then washing the basswood with deionized water several times, and placing the washed basswood in tert-butyl alcohol for 12-14 hours for solvent exchange, and then freeze-drying to obtain chemically treated basswood; S3. Preparation of flexible MXene-basswood electrode: immerse the chemically treated basswood obtained in step S2 into a nanocellulose suspension of a certain concentration, soak it in a vacuum environment for 8-12 hours to obtain a sample, take it out and freeze-dry it to obtain a freeze-dried sample; The MXene suspension prepared in step S1 is added with a certain mass of deionized water, and then ultrasonically dispersed for a certain period of time before adding the freeze-dried sample, soaking in a vacuum environment for 12-14 hours and then freeze-drying, and the soaking MXene suspension and then freeze-drying process are repeated three times to obtain a flexible MXene-basswood electrode.

2. The method for preparing a high-performance flexible wood electrode material according to claim 1, characterized in that: The etching solution in step S1 is prepared by adding 1.0 g of LiF into 20 mL of 9 M hydrochloric acid aqueous solution, and stirring at 500 rpm for 10 minutes to obtain a uniform etching solution.

3. The method for preparing a high-performance flexible wood electrode material according to claim 2, characterized in that: In step S1, the material-liquid ratio of Ti3AlC2 to etching solution is 1g:20-25ml, and the ultrasonic power is 300W.

4. The method for preparing a high-performance flexible wood electrode material according to claim 3, characterized in that: In step S2, the thickness of the natural basswood is 1-5 mm, the concentration of the potassium hydroxide solution is 5-15 wt %, and the concentration of the hydrogen peroxide solution is 15-30 wt %.

5. The method for preparing a high-performance flexible wood electrode material according to claim 4, characterized in that: The freeze-drying conditions in step S2 are 1 Pa, -50°C, and the freeze-drying time is 12-48 hours.

6. The method for preparing a high-performance flexible wood electrode material according to claim 5, characterized in that: In step S3, the concentration of nanocellulose is 0.5-0.8 wt %, the nanocellulose is cellulose with a diameter of 3-10 nm and a length of 400-800 nm, and the vacuum environment is 0.1-1.0 MPa and 25° C.

7. The method for preparing a high-performance flexible wood electrode material according to claim 6, characterized in that: In step S3, the concentration of the MXene suspension obtained by adding a certain mass of pure water to the MXene suspension prepared in step S1 is 5 mg / mL, the ultrasonic time is 10-30 minutes, the freeze-drying conditions are 1 Pa, -50°C, and the freeze-drying time is 12-48 hours.

8. A high-performance flexible wood electrode material prepared by the method for preparing a high-performance flexible wood electrode material according to any one of claims 1 to 7, characterized in that: The maximum bending angle of the electrode is 135°.

9. An application of a high-performance flexible wood electrode material prepared by the method for preparing a high-performance flexible wood electrode material according to any one of claims 1 to 7, characterized in that: Used in supercapacitors, zinc ion hybrid capacitors, lithium ion batteries, zinc batteries, zinc-air batteries, and sodium ion batteries.

10. The use of a high-performance flexible wood electrode material prepared by the method for preparing a high-performance flexible wood electrode material according to claim 9, characterized in that: The flexible MXene-basswood electrode was used as the cathode, the metal zinc plate as the anode, and the polyacrylamide / ZnSO4 gel as the electrolyte to assemble a zinc ion hybrid capacitor.

Citation Information

Patent Citations

  • A method for preparing an MXene-based flexible fabric electrode and application thereof to a supercapacitor

    CN109003836A

  • MXene wood sponge electrode with three-dimensional layered structure and preparation method and application thereof

    CN112629718A